2018
DOI: 10.1590/1678-7757-2017-0270
|View full text |Cite
|
Sign up to set email alerts
|

Model resin composites incorporating ZnO-NP: activity against S. mutans and physicochemical properties characterization

Abstract: Although resin composites are widely used in the clinical practice, the development of recurrent caries at composite-tooth interface still remains as one of the principal shortcomings to be overcome in this field.ObjectivesTo evaluate the activity against S. mutans biofilm of model resin composites incorporating different concentrations of ZnO-nanoparticles (ZnO-NP) and characterize their physicochemical properties.Materials and MethodsDifferent concentrations of ZnO-NP (wt.%): E1=0, E2=0.5, E3=1, E4=2, E5=5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
7
28
0
Order By: Relevance
“…In the presented study, the flexural strength significantly decreased only for the highest antimicrobial filler concentration, whereas the flexural modulus values were stable. Similar trends were noted for other experimental materials compounded with antibacterial particles [ 36 , 111 ]. However, for composites with calcium fluoride, after 24 h storing in wet conditions, a significant deterioration of flexural properties has been registered [ 112 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the presented study, the flexural strength significantly decreased only for the highest antimicrobial filler concentration, whereas the flexural modulus values were stable. Similar trends were noted for other experimental materials compounded with antibacterial particles [ 36 , 111 ]. However, for composites with calcium fluoride, after 24 h storing in wet conditions, a significant deterioration of flexural properties has been registered [ 112 ].…”
Section: Discussionsupporting
confidence: 87%
“…Increasing antibacterial filler concentration caused a small but systematic lowering of microhardness. This is in opposition to some findings for commercially available materials, where higher filler content was correlated with higher microhardness [ 117 ], but is in accordance with some research, where introducing antibacterial additives decreased microhardness [ 44 , 101 , 111 ].…”
Section: Discussionsupporting
confidence: 72%
“…In all of the three studies that assessed samples under electron microscopy, a qualitative reduction in the number of bacterial colonies was found with increasing ZnO-NP concentrations; however, the concentrations at which these changes were observed differed considerably amongst the three studies—1 wt % being the lowest effective loading depending on the study [ 19 , 25 , 32 ]. One of the studies measured biofilm metabolic activity and lactic acid formation, and it came to the conclusion that composites containing at least 1 wt % ZnO-NP reduce biofilm metabolic activity, but that a decrease in lactic acid production is only seen at concentrations of 5 wt % ZnO-NPs or greater [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth to mention that the degree of conversion for resins doped with trigonelline and chlorogenic acid at 50% was statistically lower than the control, and some concerns can be done in this respect. Some studies have shown an inverse correlation between solubility and degree of conversion for dental resins and composites 30‐32 . So, as the solubility is related to the leaching of compounds from the material, it can be speculated that the lower conversion could have favored the higher coffee compound release from these resins.…”
Section: Discussionmentioning
confidence: 99%